2018
DOI: 10.15446/abc.v23n2.67394
|View full text |Cite
|
Sign up to set email alerts
|

Actividad antiproliferativa de aceites esenciales de plantas cultivadas en Colombia

Abstract: RESUMENColombia posee gran diversidad de plantas medicinales, pero pocas han sido objeto de investigación. En este trabajo se evaluó la actividad antiproliferativa de aceites esenciales obtenidos por hidrodestilación asistida por microondas. Se analizaron 15 muestras de 11 especies en ensayos del MTT en células cancerosas MCF-7, HeLa y HepG-2 y se incluyeron células normales humanas (HEK293) y de animales (Vero y BF16F10) para evaluar selectividad. La composición química de muestras activas se determinó por cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 37 publications
0
8
1
Order By: Relevance
“…Likewise, the chemical compositions of the SDE extract (volatile fraction) and the EO of leaves were similar, with certain differences in the relative amounts. However, the EO composition was different from those reported by Tangarife-Castaño et al [ 13 ], Castañeda et al [ 29 ], Uztáris-Fajardo et al [ 14 ] and Velandia et al [ 20 ], whose EOs were composed of dillapiole (~39%)/β-caryophyllene (~8%), 1,8-cineole (~37%)/β-pinene (~9%) and α-pinene (~19%)/β-pinene (~16%)/β-caryophyllene (~12%)/caryophyllene oxide (~11%), respectively. It is important to mention that Muñoz [ 17 ] identified gibbilimbol B (~86%) and apiole (~4%) as the main components of the P. eriopodon EO, but from fruits.…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…Likewise, the chemical compositions of the SDE extract (volatile fraction) and the EO of leaves were similar, with certain differences in the relative amounts. However, the EO composition was different from those reported by Tangarife-Castaño et al [ 13 ], Castañeda et al [ 29 ], Uztáris-Fajardo et al [ 14 ] and Velandia et al [ 20 ], whose EOs were composed of dillapiole (~39%)/β-caryophyllene (~8%), 1,8-cineole (~37%)/β-pinene (~9%) and α-pinene (~19%)/β-pinene (~16%)/β-caryophyllene (~12%)/caryophyllene oxide (~11%), respectively. It is important to mention that Muñoz [ 17 ] identified gibbilimbol B (~86%) and apiole (~4%) as the main components of the P. eriopodon EO, but from fruits.…”
Section: Discussioncontrasting
confidence: 70%
“…and Radopholus spp.) and antioxidant (e.g., ABTS +• , DPPH • , ORAC) properties [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ], as well as chemical variability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Piper mosenii C. has no popular name or use as a medicinal plant reported in the literature [13,14]. Nevertheless, many species belonging to this genus have economic importance, besides having medicinal properties, such as antimicrobial and antiproliferative activities [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Four species out of the 15 showed activity against MCF-7 and HeLa cell lines (IC 50 50 μg/ml). GC-MS analysis revealed that β-caryophyllene was a major component in those essential oils (Velandia, Quintero, Stashenko, & Ocazionez, 2018).…”
Section: Discussionmentioning
confidence: 99%